LINGUISTIC AND PARALINGUISTIC STRATEGIES OF EXPRESSING AGREEMENT AND DISAGREEMENT IN ENGLISH AND UZBEK LANGUAGES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Agreement and disagreement are fundamental components of human communication that reflect interpersonal relationships, cultural norms, and pragmatic intentions. These communicative acts are conveyed not only through linguistic forms but also through paralinguistic and nonverbal strategies such as intonation, facial expressions, gestures, and pauses. This article investigates the linguistic and paralinguistic strategies used to express agreement and disagreement in English and Uzbek languages within a comparative framework. The research demonstrates that although English and Uzbek share several universal communicative features, they differ significantly in terms of politeness strategies, indirectness, emotional expression, and culturally specific gestures. The findings contribute to the fields of pragmatics, sociolinguistics, intercultural communication, and discourse analysis by revealing how language and culture interact in the expression of interpersonal attitudes.